Main issues of the Institute of philosophy of the National Academy of Sciences of the Kyrgyz Republic (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is devoted to the consideration of the main directions of scientific research and educational activities of the Institute of Philosophy of the National Academy of Sciences of the Kyrgyz Republic. The work reveals the key tasks facing the Institute of Philosophy of the NAS KR: conducting fundamental and applied philosophical research aimed at studying and understanding the national cultural and historical heritage of Kyrgyzstan; research of philosophical problems of the development of Kyrgyz society in the context of global transformations; development of conceptual approaches to solving urgent socio-political, ethical and ideological problems of our time; training of highly qualified personnel in the field of philosophy, capable of carrying out scientific and pedagogical activities. The authors note that the Institute of Philosophy of the National Academy of Sciences of the Kyrgyz Republic plays a leading role in preserving and developing the national philosophical school, consolidating the intellectual potential of the republic, and ensuring the continuity of philosophical traditions. The article emphasizes the scientific and social significance of the research carried out by the Institute’s staff, their contribution to the formation of ideological guidelines and value systems of Kyrgyz society.
Keywords: Institute of Philosophy, National Academy of Sciences of the Kyrgyz Republic, philosophical research, Kyrgyz culture, methodology and theory, national identity, philosophical school